A Methodology for Developing Manufacturing Process Ontologies - Akmal, Suriati (2013)
The representation of knowledge of manufacturing processes plays a key role in the reuse and sharing of knowledge in areas such as product design and process planning. One common approach for knowledge representation is ontologies. Ontologies are formal models that use mathematical logic to disambiguate and define classes of things. The reasons behind this are twofold. First, ontologies have the ability to be integrated with automated reasoning applications. Second, ontologies are also useful for enabling knowledge sharing between different knowledge-based applications. However, in the absence of systematic methods for their design, most ontologies are developed in an ad-hoc manner. This paper presents a methodology for developing manufacturing process ontologies, which combines formal concept analysis with a set of criteria for characterizing classes of processes. The application of the proposed methodology is illustrated with a case study on the development of an ontology for machining processes.